2011
DOI: 10.1016/j.pain.2011.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin elicits mechanical and cold allodynia in rodents via TRPA1 receptor stimulation

Abstract: Platinum-based anticancer drugs cause neurotoxicity. In particular, oxaliplatin produces early-developing, painful, and cold-exacerbated paresthesias. However, the mechanism underlying these bothersome and dose-limiting adverse effects is unknown. We hypothesized that the transient receptor potential ankyrin 1 (TRPA1), a cation channel activated by oxidative stress and cold temperature, contributes to mechanical and cold hypersensitivity caused by oxaliplatin and cisplatin. Oxaliplatin and cisplatin evoked glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
267
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 273 publications
(298 citation statements)
references
References 48 publications
21
267
4
Order By: Relevance
“…has been described for oxaliplatin in CHO cells. 34 As things stand today, direct data about oxidative damage induced in vivo by platin derivatives are however still lacking. Moreover, the absence of a clear oxidation target hampers the finding of more active antioxidant compounds.…”
mentioning
confidence: 99%
“…has been described for oxaliplatin in CHO cells. 34 As things stand today, direct data about oxidative damage induced in vivo by platin derivatives are however still lacking. Moreover, the absence of a clear oxidation target hampers the finding of more active antioxidant compounds.…”
mentioning
confidence: 99%
“…One final common pathway activated by the otherwise chemically heterogeneous group of molecules, such as chemotherapeutic agents, is the production of oxidative stress in different tissues and cells [147,148] and, through this effect they can potentially activate and/or sensitize the TRPA1 channel. Our recent works [103,146], however, indicated that oxaliplatin and paclitaxel do not directly gate TRPA1, as they do not cause any calcium response in primary culture of mouse or rat DRG neurons. However, Chinese hamster ovary (CHO) cells transfected with the mouse TRPA1 channel respond, with a glutathionesensitive intracellular calcium mobilization, upon challenge with oxaliplatin, whereas untransfected CHO cells do not.…”
Section: Trpa1mentioning
confidence: 92%
“…Recently, our research group has disclosed the role of TRPA1 in models of CIPN [103,146]. By both genetic and pharmacological approaches, we showed that TRPA1 entirely mediates mechanical and cold hypersensitivity induced by oxaliplatin and cisplatin [146] in mice and rats.…”
Section: Trpa1mentioning
confidence: 96%
See 1 more Smart Citation
“…The most common side effect of these drugs is chemotherapy-induced neuropathy which often leads to reduction or discontinuation of therapy [7]. Oxaliplatin is able to induce neuropathic pain through several mechanisms including the modulation of Na + channels [8], alteration in Ca 2 + homeostasis [7], production of oxygen reactive species [9] and increase in caspase-mediated apoptosis [10]. Among those, oxidative stress is a key pathological feature of neuropathic pain [11][12][13].…”
Section: Introductionmentioning
confidence: 99%